The role of endowments in the realization of peace and human rights - Sabbaghian Deloui, Jafar (2021)
The purpose of this article is to examine the role of endowments in the realization of peace and human rights. Endowment means that the property of imprisonment and its benefits should be placed in the way of God. The meaning of endowment is the permanent benefit of the endowment against the property of the endowment, and for this reason it has been called endowment, and among the benefits is the transfer of interests in the way of God and social charity. So far, several researches have been done in the field of endowments but, the study of the functions of the endowment and the role of its endowments, especially in the field of peace and human rights, has not received much attention. The basic question that has been raised and examined in this regard is that what role does endowment play in achieving peace and the standards of the third generation of human rights? The present article is a descriptive-analytical and examines the question using the library method. The results of this article indicate that positive peace focuses on health, disease and the fight against disease, poverty, social and economic inequalities, and the realization of social justice and at the same time, the components of the third generation of human rights are trying to realize such things as the right to development, the right to education and the right to occupation that due to its functions, endowment plays an important role in providing the mentioned items. In conclusion, it can be said that endowment is effective in strengthening and promoting positive peace and the components of the third generation of human rights.